A functional FePt@MOFs (MIL-101(Fe)) nano-platform for high efficient colorimetric determination of H2O2. Issue 8 (13th March 2019) - Hu, Zunfu; Yin, Yongheng; Liu, Qingyun; Zheng, Xiuwen
Abstract : Surface-modified FePt nanoparticles were loaded into metal–organic frameworks in a facile in situ way and the resulting material (FePt@MOFs NCs) acted as a high efficient colorimetric detection agent for H2 O2 . Abstract : The rapid and sensitive detection of H2 O2 is of great importance for a series of industries. In this work, surface-modified FePt nanoparticles were loaded into metal–organic frameworks (MOFs, MIL-101(Fe)) in a facile in situ way and the resulting material (FePt@MOFs NCs) acted as a high efficient colorimetric detection agent. The as-prepared FePt@MOFs NCs possess a well-defined octahedron shape and high stability in water. Via the oxidation reaction of the chromogenic substrate 4, 4′-bi-2, 6-xylidine, the obtained FePt@MOFs NCs were proved to possess prominent peroxidase-mimic activity. Under the most favorable conditions, the linear range for H2 O2 detection was 40 μM to 800 μM and the detection limit was 18.9 μM. Furthermore, FePt@MOFs NCs were successfully applied to the detection of H2 O2 in real samples such as fruit juice. The developed colorimetric sensing platform is expected to have potential for the exact detection of H2 O2 for the food, mining and bio-pharmaceutical industries, due to its high stability, sensitivity, rapidness and easy preparation.